Manajemen Strategik Keunggulan Madrasah Aliyah Negeri di Kalimantan Timur - Muchammad Eka Mahmud; Suratman Suratman (FENOMENA, 2020)
Having a specific excellence that is different to other educational institutions can be an attractiveness of madrasah. This excellence needs to be managed properly to attract societies and as one of benchmarks of educational institution qualities. Educational institutions in East Kalimantan such as MAN 2 Samarinda, MAN 2 Samarinda, MAN 2 Kutai Kertanegara, and MAN Balikpapan have implemented strategic management in managing their excellence. This research aimed to find out the excellence of each madrasah and strategic management to manage the excellence in MA in East Kalimantan. This is Field work Research with qualitative approach. Data collection techniques used observation, interviews and documentations. Data analysis techniques used a qualitative analysis technique consisting of data reduction, data model (data display), and conclusing drawing/verification. Based on data, the strategic management considering the madrasah excellence in East Kalimantan is as following: 1) Skill Program based Madrasah has an excellence in the curriculum contents as elective programs for students such as culinary art skills, fashion (sewing skills), light vehicle automotive, computer science, and welding skills. The strategic management implemented is cooperative strategy to build cooperation with and credibility from business field and industry, 2) Religious Program based Madrasah has an excellence in academic by strengthening religious matters, sciences and technology, foreign languages and yellow book. The forms of strategic management used are cooperative strategy and competitive strategy, 3) Excellent Program based Madrasah has an excellence in the students’ achievements from extracurricular activities, particularly martial arts and scientific writing competition. The forms of strategic management are the combination of cooperative strategy and competitive strategy, 4) Regular Program based Madrasah has excellent achievements in scientific writing competition and Syiar Anak Negeri program. The strategic management developed is professional extracurricular coaching by implementing strategic management of cooperative and competitive.